Effect of liver transplantation on QT-interval prolongation and impact on mortality. (1st March 2021) - Ko, Jefferson; Koshy, Anoop N.; Han, Hui-Chen; Weinberg, Laurence; Gow, Paul; Testro, Adam; Lim, Han S.; Farouque, Omar; Teh, Andrew W.
Abstract: Background: QT-interval prolongation is considered the electrophysiological hallmark of cirrhotic cardiomyopathy. However, the significance of QT-interval prolongation and how it is affected by liver transplantation (LT) remains unclear. Methods: Consecutive inpatients undergoing LT between 2010 and 2017 at a state-wide liver transplant center in Australia were included. Preoperative, early postoperative and long-term follow-up corrected QT-intervals (QTc) were manually measured by a cardiologist. QTc was calculated using the Bazett formula and QTc ≥440 milliseconds (ms) was considered prolonged. Results: Overall, 1111 ECG tracings among 408 patients (mean age 57 ± 12 years) were assessed. Pre-LT, 265 patients (65.0%) had QTc ≥440 ms and 24 patients (5.9%) had QTc ≥500 ms. In the early postoperative period, there was a significant increase in QTc compared to pre-LT (471 ± 39 vs. 452 ± 31 ms, p < 0.001) and 80 patients (20.3%) had QTc ≥500 ms. At a median of six months post-LT, there was significant reduction in mean QTc compared to pre-LT (430 ± 32 vs. 452 ± 31 ms; p < 0.001) with the QTc shortening in 73% of patients. QT-interval prolongation was not associated with postoperative complications or mortality at any time-point. Conclusion: QT-interval prolongation is common in patients with liver cirrhosis and this metric normalized in the majority within six months post-LT. A significant increase in QTc was noted early post-LT, with over 20% demonstrating QTc ≥500 ms. QT-interval prolongation was not associated with post-transplant complications or mortality. Resolution of QT-interval prolongation suggests that this feature of cirrhotic cardiomyopathy may reverse post-transplantation. Highlights: QT-interval prolongation is evident in over half of liver cirrhosis patients. Liver transplantation is a curative procedure for end-stage liver disease. The QT-interval significantly prolongs further in the early post-transplant period. The QT-interval largely resolves to within normal limits on long-term follow-up. QT-interval prolongation is not a predictor of long-term mortality.